Report on visit to four North American airlines - Hyde, D. (College of Aeronautics, 1965)
The object of the visits was to discuss the current state-of-the-art with the Engineering Departments of several North American airlines which were known to be leading the field in the application of certain advanced techniques. In the limited time available it was decided to confine the talks mainly to those topics on which the chosen operators were known to have had unique experience. This note is presented in chronological sequence and is only intended to be a record of the information gathered; no derivations, or comparisons with other operators, are made. United Air Lines were visited first and reliability programmes are detailed, although the application of critical path techniques to aircraft and engine overhaul is summarised. Continental Air Lines are noted for their use of the continuous maintenance philosophy, and this is reported next. The third visit was to Air Canada where talks ranged from the applications of operations research and electronic data processing (EDP) techniques to aircraft evaluation procedures. Finally the PanAm aircraft system reliability programme is reviewed, together with a note on their general LDP engineering and maintenance activities. A bibliography is given, although it should be appreciated that some of the items listed contain information which may be commercially secure.